Design and Analysis of a 60-GHz CMOS Doppler Micro-Radar System-in-Package for Vital-Sign and Vibration Detection - Kao, T-Y J.; Yan Yan; Tze-Min Shen; Chen, A. Y-K; Jenshan Lin (IEEE transactions on microwave theory and techniques, 2013)
This paper presents the first flip-chip-packaged and fully integrated Doppler micro-radar in 90-nm CMOS for noncontact vital-sign and vibration detection. The use of a smaller wavelength compared with previous works achieves the highly compact system for portable devices, and the radar design considerations at 60 GHz are discussed from both system and circuits points of view. The compact 60-GHz core (0.73 mm 2 ) provides a 36-dB peak down-conversion gain and transmits a radar signal around 0 dBm at 55 GHz. Quadrature generation at the intermediate frequency stage of the heterodyne receiver gives a power- and area-efficient solution to the null detection point issue, ensuring robust detection. By using single-patch antennas and without a high-power amplifier, the system demonstrates the first-pass success of human vital-sign detection at 0.3 m. The small mechanical vibration with a displacement of 0.2 mm can be detected up to 2 m away. At 60 GHz, target displacement comparable to wavelength results in strong nonlinear phase modulation and increases detection difficulties. A signal-recovery algorithm is proposed to improve the accuracy of vital-sign detection.